Yasser Arafat - Downing, David, 1946- (Chicago, Ill. Heinemann Library, 2002)
A biography of the Nobel Prize winner and president of the Palestinian National Authority, which governs the areas of the Gaza Strip and West Bank.
Age Group: Adult
Includes bibliographical references (p. 60) and index.
Keywords: Arab-Israeli Conflict; Arafat, Yasir, 1929-2004; Arafat, Yasir, 1929-2004 -- Juvenile Literature; Munazzamat Al-Tahrir Al-Filastiniyah -- Presidents -- Biography -- Juvenile Literature; Nobel prizes -- Biography; Palestinian Arabs -- Biography; Palestinian Arabs -- Biography -- Juvenile Literature; Palestinian National Authority -- Biography -- Juvenile Literature; Palestinian National Authority